A 3D shape measurement method based on novel segmented quantization phase coding. (February 2019) - Wang, Lin; Chen, Yuan; Han, Xu; Fu, Yanjun; Zhong, Kejun; Jiang, Guangyu
Highlights: A segmented quantization phase coding and decoding method is proposed. A new phase unwrapping algorithm based on segmented quantization phase coding is proposed. The proposed method can guarantee high measurement accuracy in high-frequency. The proposed method allows the measurement of both single object and isolated objects with complicated shape because of using segmented quantization phase coding method. The proposed method only needs six patterns to obtain absolute phase, the model has advantages for high-speed measurement applications. Abstract: Codeword is very important in phase unwrapping based on phase coding method. Each phase coding fringe is marked with a unique codeword and then used to determine the fringe order for absolute phase retrieval. However, the traditional phase coding method is limited by the number of codeword. To overcome this problem, a segmented quantization phase coding and decoding method is proposed to achieve absolute phase retrieval without reducing the difference between adjacent quantized phase values or increasing the quantization levels. The quantized phase is modulated by a specific coding sequence and then embedded into phase coding fringe patterns, thereby greatly improving the accuracy of the decoding. The coding creates multiple segments of the whole region and each segment embeds the special coding sequence. Through the corresponding decoding algorithm, the fringe order can be obtained, and following this, the absolute phase is obtained. Simulation and experimental results demonstrate the feasibility and superiority of the proposed method to measure both a single object and multiple isolated objects.